Conserved Intramolecular Disulfide Bond Is Critical to Trafficking and Fate of ATP-binding Cassette (ABC) Transporters ABCB6 and Sulfonylurea Receptor 1 (SUR1)/ABCC8 - Fukuda, Yu (American Society for Biochemistry and Molecular Biology, 2011)
The ATP-binding cassette (ABC) transporter ABCB6 is a mitochondrial porphyrin transporter that activates porphyrin biosynthesis. ABCB6 lacks a canonical mitochondrial targeting sequence but reportedly traffics to other cellular compartments such as the plasma membrane. How ABCB6 reaches these destinations is unknown. In this study, we show that endogenous ABCB6 is glycosylated in multiple cell types, indicating trafficking through the endoplasmic reticulum (ER), and has only one atypical site for glycosylation (NXC) in its amino terminus. ABCB6 remained glycosylated when the highly conserved cysteine (Cys-8) was substituted with serine to make a consensus site, NXS. However, this substitution blocked ER exit and produced ABCB6 degradation, which was mostly reversed by the proteasomal inhibitor MG132. The amino terminus of ABCB6 has an additional highly conserved ER luminal cysteine (Cys-26). When Cys-26 was mutated alone or in combination with Cys-8, it also resulted in instability and ER retention. Further analysis revealed that these two cysteines form a disulfide bond. We discovered that other ABC transporters with an amino terminus in the ER had similarly configured conserved cysteines. This analysis led to the discovery of a disease-causing mutation in the sulfonylurea receptor 1 (SUR1)/ABCC8 from a patient with hyperinsulinemic hypoglycemia. The mutant allele only contains a mutation in a conserved amino-terminal cysteine, producing SUR1 that fails to reach the cell surface. These results suggest that for ABC transporters the propensity to form a disulfide bond in the ER defines a unique checkpoint that determines whether a protein is ER-retained.